Violence, Science, and Cotton in Colonial-Fascist Mozambique (1934-1974) - Guimarães, Paulo Eduardo (2022)
Since the 19th century, Portuguese authorities had made unsuccessful attempts to promote cotton production in Angola and Mozambique. Under colonial fascist rule, the cotton plantations expanded significantly to meet the demands of the Portuguese textile industry. Eventually, cotton became the major agricultural export in Mozambique. This text explores the causes for this success, focusing on the rapid growth of indigenous cotton fields in northern Mozambique. In our research, we analysed contemporary "grey" cotton scientific literature, labour legislation, administration reports, agronomical thesis and the extensive collection of anthropological and social history studies carried out since the 1970s. We demonstrate that fascism created a specific model for the exploitation of humans and nature. This model involved labour mobilization based on daily physical and psychological violence and the humiliation of the indigenous people, the promotion and advancement of colonial cotton science for the industrialization of nature, and the creation of new economic institutions and rules to promote neo-mercantilist policies